2007
DOI: 10.1038/sj.jes.7500619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure measurement error on particle matter epidemiology: a simulation using data from a panel study in Baltimore, MD

Abstract: Ascertaining the true risk associated with exposure to particulate matter (PM) is difficult, given the fact that pollutant components are frequently correlated with each other and with other gaseous pollutants; relationships between ambient concentrations and personal exposures are often not well understood; and PM, unlike its gaseous co-pollutants, does not represent a single chemical. In order to examine differences between observed versus true health risk estimates from epidemiologic studies, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Recent studies have documented the potential for measurement error to bias risk estimates toward the null for pollutants with high spatial variability (Suh and Zanobetti, 2010;Van Roosbroeck et al, 2008) and previous analyzes of exposure measurement error in timeseries studies of mortality suggest that risk estimates based on fixed-site ambient air pollution data are smaller than those estimated from personal measures (Schwartz et al, 2007;Zeger et al, 2000). In this study we examined the potential impact of exposure measurement error for short-term (24-h) exposure to NO 2 on risk estimates derived from a case-crossover analysis using existing data from Windsor, Ontario (Lavigne et al, 2012;Wheeler et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have documented the potential for measurement error to bias risk estimates toward the null for pollutants with high spatial variability (Suh and Zanobetti, 2010;Van Roosbroeck et al, 2008) and previous analyzes of exposure measurement error in timeseries studies of mortality suggest that risk estimates based on fixed-site ambient air pollution data are smaller than those estimated from personal measures (Schwartz et al, 2007;Zeger et al, 2000). In this study we examined the potential impact of exposure measurement error for short-term (24-h) exposure to NO 2 on risk estimates derived from a case-crossover analysis using existing data from Windsor, Ontario (Lavigne et al, 2012;Wheeler et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Here we focus on the classical model, which typically leads to greater bias. Moreover, if fixed-site monitors systematically over or underestimate personal exposures, a scaling factor is required to further adjust model coefficients, since incremental changes in ambient concentrations translate into changes of a different magnitude at the personal level (Schwartz et al, 2007). Unfortunately, paired personal and fixed-site exposure data are rarely available in practice.…”
Section: Introductionmentioning
confidence: 99%
“…These results, therefore, suggest that multipollutant models using ambient concentrations of gases may be a form of source apportionment of the effects of particle phase pollution and may provide limited information about the effects of gases. A simulation study conducted by Schwartz et al (2007) using the Baltimore data showed that a significant association with ambient O 3 is much more likely to result from a true association with sulfate than from a true association with exposure to O 3 . However, this may not be true in all cities.…”
Section: Surrogate Measures Of Pollutant Mixturesmentioning
confidence: 99%
“…[1][2][3] The impact of air pollutants on the health of susceptible populations such as the elderly, 4 diabetics, 5 children, 6 and asthmatics [7][8][9][10] indicate that exposure sources and baseline health are important factors for guiding regulatory decisions related to ambient or indoor air quality guidelines or standards.…”
Section: Introductionmentioning
confidence: 99%